2022
DOI: 10.1186/s12905-022-02009-0
|View full text |Cite
|
Sign up to set email alerts
|

Primiparous women’s knowledge of diastasis recti abdominis, concerns about abdominal appearance, treatments, and perceived abdominal muscle strength 6–8 months postpartum. A cross sectional comparison study

Abstract: Background Diastasis recti abdominis (DRA) is a prevalent condition in the postpartum period. To date, there is scant knowledge on how DRA influences physical, mental, and emotional health. This study investigates primiparous women`s knowledge about DRA, concerns about abdominal appearance, and perceived abdominal muscle strength, comparing women with and without reported DRA. Methods This was a cross-sectional comparison study. Data were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…This may be related to contemporary women’s pursuit of an ideal body shape. Postpartum DRA induces negative emotions, which will affect patients’ participation in postpartum rehabilitation, which in turn negatively affects the repair of the rectus abdominis muscles, such as further aggravation of the separation and even injury, forming a vicious cycle[ 20 ]. In the present study, the posttreatment EPDS score in the Group L was significantly lower than that in the Group S ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to contemporary women’s pursuit of an ideal body shape. Postpartum DRA induces negative emotions, which will affect patients’ participation in postpartum rehabilitation, which in turn negatively affects the repair of the rectus abdominis muscles, such as further aggravation of the separation and even injury, forming a vicious cycle[ 20 ]. In the present study, the posttreatment EPDS score in the Group L was significantly lower than that in the Group S ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a misconception that DRA is primarily a cosmetic issue, underestimating its functional impact or potential associated dysfunctions [ 79 ]. A recent study revealed that women who were concerned with their abdominal appearance post-partum are most likely to seek advice on treatment through social media [ 80 ]. Improved communication among health care professionals is crucial for providing women with access to evidence-based women's health services.…”
Section: Discussionmentioning
confidence: 99%
“…DRA can affect spinal and pelvic stability, alter overall body posture, and increase the risk of lumbago, chronic pelvic pain, and pelvic floor dysfunction (Benjamin et al, 2019;Eriksson Crommert et al, 2020). Some studies have reported that the body image and body satisfaction rate of patients with DRA are significantly lower than those of the general population (Keshwani et al, 2018;Gluppe et al, 2022).…”
Section: Introductionmentioning
confidence: 99%